Mortality patterns of hydro-geomorphologic disasters - da Silva Pereira, Susana (2016)
Social impacts caused by floods and landslides in Portugal in the period of 1865-2010 are gathered in the DISASTER database. This database contains 1,902 hydro-geomorphologic cases that caused 1,248 fatalities (81% and 19% associated with floods and landslides, respectively). The use of the DISASTER database allowed for: (i) the analysis of the frequency and the temporal evolution of fatal floods and landslides; (ii) the analysis of the spatio-temporal distribution of fatalities; (iii) the identification of the most deadly flood and landside types; (iv) the verification of gender tendencies in mortalities; and (v) the evaluation of individual and societal risk. The highest number of flood and landslide cases and related mortalities occurred in the period of 1935-1969. After this period, the number of flood and landslide mortalities decreased, although landslide fatalities remained higher than those registered in the period of 1865-1934. The occurrence of flood fatalities was widespread in the country, with an important cluster in the Lisbon region and in the Tagus valley, while fatalities caused by landslides mainly occurred in the north of the Tagus valley. Flash floods caused the majority of fatalities associated with floods, while falls and flows were responsible for the highest number of fatalities associated with landslides. Males were found to have the highest frequency of fatalities. In the case of floods, the majority of fatalities were found both outdoors and inside of buildings in rural areas while fatalities inside buildings were dominant in landslide cases, mostly in rural areas.